Revitalizing Rural Landscapes: Transforming architecture and cultivating community anchorage through productive landscaping in Kabokweni Mpumalanga - Nkosi, Bonga Wiseman (University of the Witwatersrand, Johannesburg, 2025)
This thesis explores the revitalisation of Kabokweni, a township in Mpumalanga, South Africa, through a comprehensive architectural intervention. It addresses the socio-economic challenges of informal trading and water scarcity by integrating design strategies that create sustainable market spaces and agricultural opportunities. Additionally, a food processing facility for avocados and mangoes is incorporated, creating opportunities for skill development and employment. By introducing a portion of land for each trader to farm on-site, the project reduces transportation costs and encourages local food production. Furthermore, borehole and rainwater harvesting systems are proposed to tackle the water crisis, with water features symbolising the historical significance of the Ngodini River. The architectural design preserves the local trading culture by maintaining the use of building perimeters for trade, fostering economic growth while strengthening the connection between the community and their environment. The facility also incorporates training centres to equip locals with essential skills, creating employment opportunities and economic resilience. By balancing the formalisation of trading spaces with the preservation of informal practices, this project aims to improve the livelihoods of local traders, provide a sense of place, and foster sustainable economic development within Kabokweni.
This research report is submitted in partial fulfillment for the degree of Master of Architecture (Professional), to the Faculty of Engineering and Built Environment, School of Architecture and Planning, University of the Witwatersrand, Johannesburg, 2025
Keywords: Revitalizing Rural Landscapes; Agricultural Produce; Mangoes; Planting; Avocado; Small shop; Socio-economic challenges; Informal trading; Kabokweni; Mpumalanga; Water scarcity; Ngodini River; UCTD; SDG-15: Life on land; SDG-11: Sustainable cities and communities